2013
DOI: 10.1186/1472-6882-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Morus alba and active compound oxyresveratrol exert anti-inflammatory activity via inhibition of leukocyte migration involving MEK/ERK signaling

Abstract: BackgroundMorus alba has long been used in traditional Chinese medicine to treat inflammatory diseases; however, the scientific basis for such usage and the mechanism of action are not well understood. This study investigated the action of M. alba on leukocyte migration, one key step in inflammation.MethodsGas chromatography-mass spectrometry (GC-MS) and cluster analyses of supercritical CO2 extracts of three Morus species were performed for chemotaxonomy-aided plant authentication. Phytochemistry and CXCR4-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 48 publications
0
57
0
Order By: Relevance
“…There are many reports on the uses of mulberry leaves, such as the suppression of hyperglycemia and atherosclerosis, as well as their antioxidant, antineoplastic, anti‐inflammatory and anti‐obesity effects. 1‐Deoxynojirimycin (DNJ), a functional component of mulberry, is known to inhibit the elevation of blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports on the uses of mulberry leaves, such as the suppression of hyperglycemia and atherosclerosis, as well as their antioxidant, antineoplastic, anti‐inflammatory and anti‐obesity effects. 1‐Deoxynojirimycin (DNJ), a functional component of mulberry, is known to inhibit the elevation of blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…This result was compared with the previous study of oxyresveratrol extraction on literature, as seen in Table 2 EA fraction of M. alba branch yield was 1.89% (Chen et al, 2013). Oxyresveratrol from barks and roots methanolic extract calculated with HPTLC method was 0.27%, and 0.30%, and was not identified in leaves, fruits, or xylem (Ayinampudi et al, 2011) and from stems ethanolic extract calculated with HPLC was 17.87 ± 0.61% with yield 5.13% (Zeng et al, 2010).…”
Section: High-performance Liquid Chromatography (Hplc) Analysis Of Oxmentioning
confidence: 74%
“…Recently, it has been reported that oxyresveratrol has an anti-inflammatory activity through inhibition of leukocyte migration. This is caused by inhibition of MEK/ERK pathway (Chen et al 2013). In addition, oxyresveratrol has a neuroprotective activity and inhibits the apoptotic cell death in transient rat middle cerebral artery occlusion (MCAO) model of brain ischemia.…”
Section: Discussionmentioning
confidence: 99%